2014
DOI: 10.3233/bme-141041
|View full text |Cite
|
Sign up to set email alerts
|

Improving pilot mental workload evaluation with combined measures

Abstract: Behavioral performance, subjective assessment based on NASA Task Load Index (NASA-TLX), as well as physiological measures indexed by electrocardiograph (ECG), event-related potential (ERP), and eye tracking data were used to assess the mental workload (MW) related to flight tasks. Flight simulation tasks were carried out by 12 healthy participants under different MW conditions. The MW conditions were manipulated by setting the quantity of flight indicators presented on the head-up display (HUD) in the cruise p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 14 publications
1
34
0
1
Order By: Relevance
“…NASA-TLX (Hart and Staveland 1988) (Backs, 1994;Brookings et al, 1996;Durantin et al, 2014;Fairclough et al, 2005;Fallahi et al, 2016;Fournier et al, 1999;Gao et al, 2013;Hankins and Wilson, 1998;Hoepf et al, 2015;Hsu et al, 2015;Hwang et al, 2008;Lee and Liu, 2003;Lehrer et al, 2010;Luque-Casado et al, 2016;Matthews et al, 2015;Miyake, 2001;Miyake et al, 2009;Ryu and Myung, 2005;Sauer et al, 2013;Sirevaag et al, 1993;Svensson and Wilson, 2009;Wanyan et al, 2014) 22 RSME (Zijlstra 1993) (Hogervorst et al, 2014;Hsu et al, 2015;De Rivecourt et al, 2008;Veltman and Gaillard 1996;Veltman and Gaillard 1998;Veltman 2002) 6…”
Section: Inclusion Criteriaunclassified
See 1 more Smart Citation
“…NASA-TLX (Hart and Staveland 1988) (Backs, 1994;Brookings et al, 1996;Durantin et al, 2014;Fairclough et al, 2005;Fallahi et al, 2016;Fournier et al, 1999;Gao et al, 2013;Hankins and Wilson, 1998;Hoepf et al, 2015;Hsu et al, 2015;Hwang et al, 2008;Lee and Liu, 2003;Lehrer et al, 2010;Luque-Casado et al, 2016;Matthews et al, 2015;Miyake, 2001;Miyake et al, 2009;Ryu and Myung, 2005;Sauer et al, 2013;Sirevaag et al, 1993;Svensson and Wilson, 2009;Wanyan et al, 2014) 22 RSME (Zijlstra 1993) (Hogervorst et al, 2014;Hsu et al, 2015;De Rivecourt et al, 2008;Veltman and Gaillard 1996;Veltman and Gaillard 1998;Veltman 2002) 6…”
Section: Inclusion Criteriaunclassified
“…Total: 38 (Backs, 1994;Bernardi et al, 2000;Boutcher and Boutcher, 2006;Causse et al, 2010;Delaney and Brodie, 2000;Finsen et al, 2001;Hogervorst et al, 2014;Holland and Tarlow, 1972;Luque-Casado et al, 2016;Miyake et al, 2009;Nickel and Nachreiner, 2003;Reiner and Gelfeld, 2014;Ryu and Myung, 2005;Schellekens et al, 2000;Tripathi et al, 2003;Zhang et al, 2010) 16 Simulated fixed wing operations (Braby et al, 1993;Dussault et al, 2005;Fairclough et al, 2005;Fairclough and Venables 2006;Fournier et al, 1999;Hsu et al, 2015;Lahtinen et al, 2007;Lee and Liu 2003;Lehrer et al, 2010;Mansikka et al, 2016a;Mansikka et al, 2016b;Miyake 2001;Prinzel et al, 2000;De Rivecourt et al, 2008;Svensson and Wilson 2009;Tattersall and Hockey 1995;Veltman and Gaillard 1996;Veltman and Gaillard 1998;Wang et al, 2016;Wanyan et al, 2014) 19 Fixed-wing operations (Dussault et al, 2004;Hankins and W...…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Mean pupil diameter was sensitive to workload, and it increased gradually with the increase of workload. It indicated that a further resource was needed to deal with the increase of workload [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some past studies have investigated the reliability of using a combined approach to assess mental workload for computerized tasks and simulated conditions in other domains (Cegarra & Chevalier, ; Luque‐Casado, Perales, Cárdenas, & Sanabria, ; Wanyan, Zhuang, & Zhang, ). Luque‐Casado et al () investigated HRV as a function of cognitive demands (based on the NASA‐TLX ratings) in several computerized tasks.…”
Section: Introductionmentioning
confidence: 99%